2007
DOI: 10.1016/j.jpeds.2007.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cognitive Deficits in Young Children with Cystinosis: Evidence for an Early Effect of the Cystinosin Gene on Neural Function

Abstract: The same pattern of visual spatial deficit is present in young children with cystinosis as has previously been demonstrated in older children and adults, which suggests that there may be an influence of the cystinosis gene on brain development, rather than an adverse effect of prolonged cystine accumulation in the brain during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
0
28
1
Order By: Relevance
“…found that Children with cystinosis performed significantly more poorly on tests of visual Spatial and visual motor function than did controls. This deficit is associated with intact visual perception, but impaired spatial processing and memory[7,8], and is associated with deficits in mathematical skills[9]. Young children with cystinosis demonstrated a discrepancy such that non-verbal IQ indices (Performance IQ and Processing Speed Index) were significantly lower than verbal IQ indices[10].…”
Section: Discussionmentioning
confidence: 99%
“…found that Children with cystinosis performed significantly more poorly on tests of visual Spatial and visual motor function than did controls. This deficit is associated with intact visual perception, but impaired spatial processing and memory[7,8], and is associated with deficits in mathematical skills[9]. Young children with cystinosis demonstrated a discrepancy such that non-verbal IQ indices (Performance IQ and Processing Speed Index) were significantly lower than verbal IQ indices[10].…”
Section: Discussionmentioning
confidence: 99%
“…Neurological co-morbidity was the most negative predictor of poor motor performance [41]. It has been suggested that mutations in the CTNS gene may influence brain development [42]. However, at least two studies have been unable to find a correspondence between intellectual development and cognitive functioning and the degree of observed cerebral atrophy [39,43].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly reported have been neurobehavioral abnormalities and motor disturbances. Cognitive and behavioral abnormalities are frequently observed in children with cystinosis [13][14][15]. A unique impairment in visuospatial perception has been observed in even very young children with cystinosis suggesting that some cognitive deficits may be result from the gene defect on brain development rather than arising from prolonged cystine accumulation [15].…”
Section: Discussionmentioning
confidence: 99%